Truly, madly, deeply : a novel / Karen Kingsbury. - Kingsbury, Karen (Atria Paperback, 2021)
When eighteen-year-old Tommy Baxter declares to his family that he wants to be a police officer after graduation, his mother, Reagan, won't hear of it. After all, she's still mourning the death of her own father on September 11 and she's determined to keep her son safe from danger. But Tommy's father, Luke, is proud of Tommy's decision. He would make a kind and compassionate cop. Meanwhile, Tommy is in love for the first time. His sweet relationship with Annalee Miller is almost too good to be true. Tommy begins seriously thinking about the far off day when he can ask her to marry him but she hasn't been feeling well. Tests reveal the unthinkable. While his girlfriend begins the fight of her life, Tommy is driven to learn more about the circumstances surrounding his birth and the grandfather he never knew.